Do Entrepreneurship Education and Family Experience Promote Student's Entrepreneurial Intention? The Mediating Role of Unemployment Rate : An Integrated Analysis through Entrepreneurship Theory, Social Learning Theory, and Hidden Unemployment Theory - Prety Diawati; Okta Karneli; Siminto Siminto; Andri Pitoyo; Loso Judijanto (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This research aims to examine the relationship between entrepreneurship education, family experience, and students' entrepreneurial intentions, exploring the mediating role of the unemployment rate. Three theories were integrated into this study: Entrepreneurship Theory, Social Learning Theory, and Hidden Unemployment Theory. The study utilized a quantitative approach, employing structural equation modeling (SEM) and Partial Least Square (PLS) for analysis, as well as correlation analysis to examine relationships between variables. Non-probability sampling technique used is Purposive Sampling to determine the research sample. The study participants consisted of 100 college students in Bandung City, Indonesia, selected to complete an online questionnaire. The findings indicate that entrepreneurship education and family experience significantly and positively impact students' entrepreneurial intentions. Furthermore, the unemployment rate serves as a positive mediator in the relationship between entrepreneurship education and entrepreneurial intentions. Entrepreneurship education empowers individuals to create self-employment opportunities, reduces the unemployment rate, motivates students to pursue entrepreneurial paths, and shapes the entrepreneurship education curriculum to meet evolving market demands.